Precise edge functionalization and tailoring of graphene via solvent-controlled reactions. (September 2022) - Li, Mingyao; Zhou, Shuyao; Ren, Shizhao; Zhang, Lei; Yin, Bing; Zhao, Cong; Liu, Zhirong; Jia, Chuancheng; Guo, Xuefeng
Abstract: Controllable edge-selective modification and tailoring of graphene are particularly critical for graphene applications. In this study, precise edge functionalization and tailoring of graphene are realized by a solvent-controlled Friedel-Crafts acylation reaction. Specifically, experimental and theoretical studies demonstrate that solvent effects can effectively control the reaction pathways of substituent and ionic mechanisms. Under the substituent mechanism, carboxyl groups are accurately introduced to the edge of graphene, which can be used as new reaction sites for further modification. Under the ionic mechanism, the acylation process can further tear graphene to the desired size. When the reaction is sufficient, graphene can be torn into highly dispersed high-quality quantum dots on a scale of 5 nm. This edge- and size-controllable fabrication method expands potential applications of graphene, such as electronic devices, semiconductors, catalysis and batteries. Graphical abstract: Precise edge-selective functionalization and tailoring of graphene are achieved through solvent-controlled Friedel–Crafts acylation reactions under ionic or substituent mechanisms. Under the substituent mechanism, edge-selective functionalized graphene can be prepared. Under the ionic mechanism, C–C bonds of graphene can be broken to generate modified graphene with controllable size, and thus high-quality graphene quantum dots are prepared at the same time. Image 1 Highlights: Friedel-Crafts acylation of graphene is controllably carried out via solvent effects under ionic or substituent mechanisms. Precise edge-selective modification and tailoring of graphene are both achieved for the first time based on two mechanisms. High-quality graphene quantum dots with water-soluble carboxyl groups are prepared by chemical tailoring of graphene.